ANALISIS KESESUAIAN LAHAN DAN KELAYAKAN EKONOMI BEBERAPA TANAMAN PANGAN PADA LAHAN BERBATU DI KECAMATAN GU KABUPATEN BUTON TENGAH - RUSTAM, LA ODE; ALAM, SYAMSU; ALWI, LA ODE; BANDE, LA ODE SANTIAJI; ZULFIKAR, ZULFIKAR; MPIA, LA (Jurnal Agroteknos, 2024)
Analysis of land suitability and economic feasibility is a way that can be done to plan the development of food crops on rocky land. The research was carried out in Gu District, Central Buton Regency and soil analysis was carried out at the Integrated Laboratory of Halu Oleo University. The research method is a free survey method, land observation type is through drilling and socio-economic data is collected through filling out questionnaires and interviews with farmers. Land suitability analysis is carried out in actual conditions and land suitability after improvements have been made. The assessment is carried out by matching land characteristics with plant growth requirements. The economic parameter used to assess the feasibility of farming annual crops is the ratio of revenue to total production costs Revenue Cost Ratio (R/C). The results of the research show that the development of food crops is based on an analysis of land suitability and financial feasibility, namely the very suitable and very feasible category reaching 485.68 Ha, quite suitable and quite feasible reaching 3,568.69 Ha and not suitable and not feasible reaching 2,305.88 Ha. Directions for planting field rice, corn or soybeans by applying liming technology, applying organic material, nitrogen and phosphorus fertilization, making terraces and planting in the direction of the contour.